Detection of IgG in cerebrospinal fluid for diagnosis of neurocysticercosis: evaluation of saline and SDS extracts from Taenia solium and Taenia crassiceps metacestodes by ELISA and immunoblot assay - Barcelos, ISD; Mineo, JR; Silva, DAD; Ferreira, M. S.; de Moura, L. P.; Biondi, Germano Francisco [UNESP]; Costa-Cruz, J. M. (Blackwell Science, 2001)
We compared saline (S) and sodium dodecyl sulphate (SDS) extracts from Taenia solium (homologous species - HO) and Taenia crassiceps (heterologous species - HE) metacestodes in order to detect Ige by ELISA and immunoblot assay (IBA) in cerebrospinal fluid (CSF) for the diagnosis of human neurocysticercosis (NC). CSF samples were obtained from 93 patients. of these, 40 had NC, five had a diagnosis of probable NC, nine had central nervous system schistosomiasis or strongyloidiasis and 39 had other neurological alterations. Samples were analysed by ELISA and the results were compared with IBA in all samples with confirmed and probable NC diagnosis, in all samples with other central nervous system parasitic infection, and in 10 of those with another neurological alterations. ELISA sensitivity was 100%, 85%, 95% and 87.5% for the S-HO, S-HE, SDS-HO and SDS-HE extracts, respectively, and ELISA specificity was 100% for S-HO, S-HE, SDS-HO extracts and 97.9% for SDS-HE antigen. Immunodominant peptides detected by IBA were, by decreasing percentage of recognition: 64-68 and 45 kDa for S-HO; 108-114, 92-95, 64-68, 83 and 88 kDa for S-HE; 64-68, 108-114, 77 and 86 kDa for SDS-HO; and 108-114, 88 and 92-95 kDa for SDS-HE. Overall the homologous antigenic extracts showed higher sensitivity than the heterologous extracts in the diagnosis of NC in CSF samples. The heterologous extracts contained most of the immunodominant peptides presented in the homologous extracts, which are recognized by Ige antibodies in CSF samples.
Keywords: Taenia solium; Taenia crassiceps; cysticercosis; immunodiagnosis; ELISA; immunoblot assay